New potential of ACE inhibitors in clinical practice - D. V. Nebieridze; A. S. Safaryan (Кардиоваскулярная терапия и профилактика)
The paper reviews the results of the studies demonstrating new potential of ACE inhibitors. The traditional clinical niche for ACE inhibitor therapy (arterial hypertension, heart failure, diabetic nephropathy) has been extended recently. Substantial vasoprotective effect of these medications has an important role in decelerating progression of atherosclerotic cardiovascular pathology. In addition, a differential assessment of protective effects, together with prognosis improvement among high-risk patients, is presented for various ACE inhibitors.